1,8-Dihydroxy-2,4,5,7-tetranitro-9,10-anthraquinone - Armaghan, M.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The ring system in the title compound, C(14)H(4)N(4)O(12), is essentially planar (r.m.s. deviation of the carbon atoms = 0.085 angstrom); the two hydroxy groups form intramolecular hydrogen bonds to the same carbonyl O atom. The nitro groups are twisted with respect to the mean plane of the ring system by 74.3 (1) (1-nitro), 42.3 (3) (3-nitro), 45.7 (3) (6-nitro) and 66.9 (1)degrees (8-nitro).